Bruno, chief of police - Walker, Martin, 1947 January 23- (Walker, Martin, 1947 January 23- Bruno series, 2010)
Meet Benoit Courréges, affectionately named Bruno, chief of police in a small village in the South of France where the rituals of the café still rule. A former soldier, Bruno has embraced the slow rhythms of country life. But the murder of an elderly North African who fought in the French army galvanizes his attention: the man had a swastika carved into his chest. When a visiting scholar helps untangle the dead man's past, Bruno's suspicions turn toward a motive more complex than hate, back to a tortured period of French history.